Myocardial Injury at Early Stage and Its Association With the Risk of Death in COVID-19 Patients: A Hospital-Based Retrospective Cohort Study - Fu, Lin; Li, Xiu-Yong; Fei, Jun; Xiang, Ying; Xiang, Hui-Xian; Li, Meng-Die; Liu, Fang-Fang; Li, Ying; Zhao, Hui; Xu, De-Xiang (Frontiers in Cardiovascular Medicine, 2020)
Background: There are growing evidence demonstrating that coronavirus disease 2019 (COVID-19) is companied by acute myocardial injury. However, the associations of SARS-CoV-2-induced myocardial injury with the risk of death and prognosis after discharge in COVID-19 patients are unclear. Methods: This prospective cohort study analyzed 355 COVID-19 patients from two hospitals in different regions. Clinical and demographic information were collected and prognosis was followed up. Results: Of 355 hospitalized patients with COVID-19, 213 were mild, 90 severe and 52 critically ill patients. On admission, 59(16.7%) patients were with myocardial injury. Myocardial injury was more popular in critically ill patients. Univariate and multivariate logistic regression revealed that male, older age and comorbidity with hypertension were three crucial independent risk factors predicting myocardial injury of COVID-19 patients. Among 59 COVID-19 patients with myocardial injury, 25 (42.4%) died on average 10.9 day after hospitalization. Mortality was increased among COVID-19 patients with myocardial injury (42.4% vs 3.38%, RR=12.542, P<0.001). Follow-up study observed that 4.67% COVID-19 patients with myocardial injury were not fully recovered in 14 days after discharge. Conclusion: Myocardial injury at early stage elevates mortality of COVID-19 patients. Male elderly patients with hypertension are more vulnerable to myocardial injury. SARS-CoV-2-induced myocardial injury has not completely recovered in 14 days after discharge.